Regeneration Status and Population Structure in Terai Community Forest: Evidence from Kalyankot Community Forest, Kapilvastu District, Nepal - Chhetri, Vivek Thapa; Shrestha, Susmita; Parajuli, Shweta; Jha, Pabitra (International Journal of Environment, 2023)
The regeneration status of a forest is an essential metrics to assess the regeneration potential and population structure of forests. In emerging nations like Nepal, however, human dependency on forests has had a negative influence on forest diversity and sustainability. This paper analyzes the regeneration status and its link with bio-physical aspects and human disturbances. The data were collected using a systematic random sampling method and sample plots were established using the fishnet tool in ArcGIS. An inventory survey of 96 plots was carried out with nested circular sample plots with a main radius of 1261 cm. The overall regeneration condition of the forest was found to be in good condition according to Community Forestry Inventory Guideline, 2004. The majority of the tree species were determined to have a sound quality and medium (II) grades in this study. In terms of the diameter class distribution, lower diameter classes (21-60 cm) comprised more adults than the upper diameter classes (61-120 cm). This study found no significant variations in the effects of biophysical factors, such as slope and aspect, on species regeneration. The study concludes the inadequate silvicultural management interventions in the forest. This information can be useful to devise systematic plans to promote good-quality regeneration and manage the factors that are likely to affect the overall regeneration. Further research focusing on other biophysical factors as well as social factors and their influence on regeneration including its management techniques is recommended.